DEVELOPMENT OF THE MODERN MARKET OF BIOENERGY – THE DRIVER IN INCREASED COMPETITIVENESS OF THE UKRAINIAN ECONOMY - Nadiia Hryshchuk (Green, Blue and Digital Economy Journal, 2022)
The purpose of the work is to study the development of the bioenergy market to determine its role and place in increasing the competitiveness of the Ukrainian economy, to determine the priority financial programs for financing alternative energy. Methodology. Theoretical and methodological basis of the study are general and special methods of scientific knowledge: generalization, analogy, analysis and synthesis, induction and deduction (to clarify the conceptual apparatus, theoretical generalizations of research results, conclusions and proposals); economic-statistical, tabular research method is used. Results. Theoretical, methodological approaches to the development of bioenergy are substantiated. The understanding of the essence of the concept of "bioenergy" is revealed and the ecological-economic and legal aspects of development of the agricultural sector of the economy on the basis of combination of economic and ecological interests are analyzed. Analytical assessment of the types of financial security showed that attracting different types of financial resources will improve the ability to gain a competitive position in the bioenergy market. Practical consequences. According to the results of the research, priority areas for improvement have been identified. Bioenergy crops are an important component of Ukraine's bioenergy potential. Their cultivation will have a number of positive effects, including: replacement of natural gas, which will improve the balance of payments of our state; the possibility of reducing the heat tariff, which will contribute to economic security, through a balanced and sound public policy to support economic activity and implement the proposed recommendations for businesses and authorities.